The Moslem as Minority Community in Democracy Process (An Analysis of the Regional Election Dynamics in Toraja Regions) - Sukri Tamma; Ismah Tita Ruslin (Universitas Islam Negeri Alauddin Makassar, 2016)
This paper aims to showed the inclination that occur in democratic process associated with the presence democratization in the “Era Reformasi”. This era begin as soon as the end of Suharto regime in 1998 that considered to brought Indonesia into democratic period which also occur in the local level. One thing that considered as effort to achieve democracy is the implementation of Decentralization via the Regional Autonomy that was regulated thru some regulations, where today the new law is the Law No. 23 year 2014. That Laws gives more opportunity to the local people to manage their area based on their objectives context. It makes some local issues including local identity became important aspect in the regional social political dynamics including in the regional election. Through the directly electoral system where people vote became the most important factor of the results, some local context then becomes prominent aspects in the process. When a region occupy by non-moslem or the Christian as like as the Toraja lands consequently issues related to the Christianity becomes important thing during the election. That condition than becomes problematic for the non-mosleem people that also have rights to vote or to be voted based on the democracy values and the laws with the fact that they are the minority in that regions. Pictures from the Toraja regional election then showed tendency on how the moslem people positioned theirselves as minority in the political dynamics of the Christian majority land and what its implication to the social politics construction in this regions. Finally fact from toraja’s land will show whether a unique condition as the contextual experience of the mosleem community as minority in particular region while in fact they are the majority in the nation.